Konsep Seni dan Keindahan M. Iqbal - Soleh, A. Khudori (el Harakah: Jurnal Budaya Islam, 2008)
Generally, art work is divided in two great sects: expressionism and functionalism. The first sect is based on the interest in the art itself, whereas the second sect links its work to others, such as social problem in the surroundings. The art concept of Iqbal seems to adopt two sects, expressionism and functionalism. With expressionism,-Iqbal asserted that an art must constitute a creation of creativities and be originally from the artist him/herself not from a repetition or imitation. On functionalism, Iqbal stated that an art is not free from the certain purposes which must be morally achieved.-Finally, based on his own concept, Iqbal maintains certain criteria and purposes which have to be in an art work. Those criteria are: 1) art must be a creative work, and 2) the creativities must be original and not the result of plagiarism. In addition, the purposes and the functions that must be guaranteed are: 1) to create the missing thing to the life in hereafter or immortality, 2) to give cultivation for human being in the world, and 3) to give motivation for people progression.  Umumnya, karya seni terbagi dalam dua sekte besar: ekspresionisme dan fungsionalisme. Sekte pertama didasarkan pada kepentingan dalam seni itu sendiri, sedangkan sekte kedua menghubungkan pekerjaannya dengan orang lain, seperti masalah sosial di sekitarnya. Konsep seni Iqbal tampaknya mengadopsi dua sekte, ekspresionisme dan fungsionalisme. Dengan ekspresionisme, -Iqbal menegaskan bahwa sebuah seni harus merupakan penciptaan kreativitas dan berasal dari seniman itu sendiri bukan dari pengulangan atau tiruan. Pada fungsionalisme, Iqbal menyatakan bahwa sebuah seni tidak terlepas dari tujuan tertentu yang harus dicapai secara moral.-Akhirnya, berdasarkan konsepnya sendiri, Iqbal mempertahankan beberapa kriteria dan tujuan yang harus ada dalam sebuah karya seni. Kriteria tersebut adalah: 1) seni harus menjadi karya kreatif, dan 2) kreativitas harus asli dan bukan hasil plagiarisme. Selain itu, tujuan dan fungsi yang harus dijamin adalah: 1) Menciptakan hal yang hilang bagi kehidupan di akhirat atau keabadian, 2) memberi kultivasi bagi manusia di dunia, dan 3) memberi motivasi bagi perkembangan orang.